Visual Disturbances as an Early Important Sign of Brain Tumor: A Case Report (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Purpose: to raise attention for careful evaluation of ocular signs and symptoms, especially mild visual disturbances, for early detection of brain tumors. Case Presentation: A 45-year-old woman presented with a one-month history of gradual vision loss in both eyes. There was also a history of headache for over a year before the vision loss symptom appeared. There was no history of trauma, ocular pain, eye redness, or lacrimation. The visual acuity (VA) of both the right and left eyes with the best-corrected visual acuity (BCVA) was 6/30. Confrontation visual field test of both eyes revealed unremarkable results upon examination. The intraocular pressures (IOP) of both eyes were 11 mm Hg. Anterior segment examination of both eyes was within normal limit except for the direct light reflexes were decreased. Relative afferent pupillary defect (RAPD) of both eyes was difficult to assess. Fundoscopy examination of both eyes revealed papilledema. The retinal fields and macula were normal bilaterally. Computerized tomography (CT) scan demonstrated a hyperdense and calcified lesion in the right frontal lobe. The dimensions of the lesion were measured as 69.9 x 52.1 mm. After contrast, the CT scan showed a strongly enhanced lesion with thickening of the right frontal bone. Both of the anterior horns of the lateral ventricle were pressed by the lesion. There was a midline shift to the left by approximately 14 mm. Both of the eyes were within normal limits. Conclusion: Blurred vision and other visual disturbances are common early symptoms in brain tumors, but diagnosis is not made till very late due to late presentation. Early detection of a brain tumor through ocular signs and symptoms and complete neuro-ophthalmic evaluation can help in early diagnosis and appropriate management of brain tumors..